EVALUATION OF HAEMATOLOGICAL CHANGES IN PARASITIC HELMINTHS AND PROTOZOA INFECTIONS IN DOGS (CANIS LUPUS FAMILIARIS, LINNAEUS, 1758) - De Andrade Silva, Bruno J. (2010)
In the present study complete blood cell count was performed in samples from 100 dogs positive for helminths and/or protozoa in fecal examination, to identify possible abnormalities related to intestinal parasitism. For parasitological diagnosis, the samples were subjected to the sieving method and further analyzed through the techniques of Willis, Faust and Hoffman. The blood counts were performed with the aid of an automated hematology analyzer and morphological evaluation by blood smear stained with rapid Panotic kit using optical microscopy bright field. The analysis of fecal samples revealed that the parasite Ancylostoma sp. was more frequent (42%), followed by Cystoisospora sp. (20%), Giardia sp. (20%), Giardia and Cystoisospora (4%), Toxocara sp. (3%), Ancylostoma and Giardia (3%), Dipylidium caninum (Linnaeus, 1758) (2%), among others (6%). The most common abnormalities found were anemia, thrombocytopenia and leukocytosis, in both helminth and protozoa infections. None of the dogs parasitized by protozoa showed blood eosinophilia, only those with helminths infections. All animals studied showed negative results in search of blood hematozoa through of buffy coat preparation. The changes observed in infected animals can serve as an indicator of the presence of parasites, thus these data can be used in conjunction with fecal diagnostic techniques, to obtain a better assessment of the severity of parasitism in the host.